The Influence of the Mother of the Mattress Song on the Profile of Pancasila Students in Grade 1 Students in Independent Curriculum Elementary Schools - Chalifalillah Chalifalillah; Mas Roro Wahyu Diah Lestari (Jurnal Indonesia Sosial Teknologi, 2025)
Character education is an important aspect in elementary school learning, especially in forming the Pancasila Student Profile according to the Merdeka Curriculum. One innovative method that can be used is the use of children's songs as a learning medium. This study aims to analyze the effect of using the song "Ibu Kasur" on the formation of the Pancasila Student Profile in grade 1 elementary school students. This study uses a quantitative method with a quasi-experimental design involving two groups, namely the experimental class and the control class. Data collection techniques are carried out through pre-test and post-test tests, observation, and documentation. Data analysis techniques include normality tests (Shapiro-Wilk), homogeneity tests (Levene's Test), Paired Sample T-Test tests, Independent Sample T-Test tests, and descriptive analysis. The results of the study showed that there was a significant increase in students' understanding of the values ​​of the Pancasila Student Profile after being given learning using the song "Ibu Kasur". This is proven by the results of the Paired Sample T-Test which showed a significance value (Sig.) <0.05, as well as a comparison of post-test scores between the experimental and control groups which showed a significant difference (Sig. <0.05 in the Independent Sample T-Test). In conclusion, the use of children's songs as a learning medium is effective in improving students' understanding of character values ​​in the Pancasila Student Profile. These findings can be a reference for educators in developing innovative and enjoyable learning methods.